Bulging Bifurcation in Residually Stressed Cylindrical Double-layered Thick-walled Cylinders Applicable to the Modeling of Arteries - Soheil Moradalizadeh; Hojjat Nazari; Heiko Topol; José Merodio (Journal of Applied and Computational Mechanics)
Experiments have shown that the unloaded state of arteries may not be the stress-free state of arterial soft tissue. These initial stresses that also exist in the unloaded state are denoted as residual stresses. Many articles on the influence of these prestresses and the initiation and propagation of instabilities in inflated cylinders restrict their considerations to a single-layer wall. This work considered a double-layered tube that is subjected to such residual stresses. The results from this work show that the combined loading from an inflation pressure, an axial stretch, and the distribution of these residual stresses in the cylinder wall may result in various instability phenomena. At relatively large axial stretches, a single bulge may occur in the center, or multiple bulges may be initiated at different locations such as the end of the cylinder, or the ends and the center of the cylinder. At a smaller amount for the axial stretches, the inflated cylinder will face a bending instability with subsequent initiation of a bulge.